Den "äckelsköna" döden: Bilder av döendet i dagens sjukvård - Magnússon, Finnur (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1996)
The purpose of this article is to analyze images and narratives of dying in the Swedish health care system. The main question is how the death of patients is dealt with and spoken of at wards and hospitals in contemporary society. Modern thoughts on death and dying are mirrored in several different narratives and assumptions. On a general level we meet the idea that modern man has been deprived of the right to his or her own death. Death has become a matter of medical technology, enclosed in medical institutes. Death has become a threat to some main features of modernity; rationality, the ability to transcend, control of one’s body and soul, the creation of self-identity and reflexivity. But at the same time changes in images of death mirror the longing for intimacy and authenticity so prevalent within modern society, as has been pointed out in the works of Anthony Giddens and Alberto Melucci. Death is the painful point where lives come to an end and dreams are scattered, while at the same time offering the opportunity for relatives and hospital staff to explore fields of authenticity and intimacy. Both these images of death should be seen as tendencies towards a change within the general discourse of death, where medical or pathological truths yield to images of death as a cultural and social construction.